Construction of 1H-indazoles from ortho-aminobenzoximes by the Mitsunobu reaction. Issue 37 (12th September 2019) - Conlon, Ivie L.; Konsein, Katie; Morel, Yulemni; Chan, Alexandria; Fletcher, Steven
Graphical abstract: Highlights: The synthesis of 1 H -indazoles from ortho -aminobenzoximes by Mitsunobu chemistry. Secondary amines are suitable substrates, as well as Boc-activated primary amines. Simple access to N 1 -protected, or N 1 -alkylated 1 H -indazoles. 1 H -indazoles may be prepared with or without substitution at the 3-position. The chemistry is compatible with several functional groups. Abstract: Recently, there has been an upsurge in the occurrence of the indazole motif in drug discovery. Accordingly, newer, milder and more efficient routes towards their synthesis have emerged in the literature. We recently reported the Mitsunobu-triggered cyclodehydration of salicylaldoximes to transient 1, 2-benzisoxazoles, and salicylhydroxamic acids to their corresponding 3-hydroxybenzisoxazoles. We hypothesized subjecting ortho -aminobenzoximes to Mitsunobu conditions will likewise induce a cyclodehydration to deliver the corresponding 1 H -indazoles. Indeed, secondary anilines afforded the predicted N 1 -substituted 1 H -indazoles, and primary anilines, after activation with a Boc group, furnished the N 1 -Boc 1 H -indazoles in good to excellent yields. This work further expands the chemical repertoire of the Mitsunobu reaction, representing its unprecedented use in the construction of the 1 H -indazole nucleus.